Relapse of chronic melioidosis in a paediatric cystic fibrosis patient: first case report from Malaysia - Mariappan, Vanitha; Thavagnanam, Surendran; Vellasamy, Kumutha Malar; Teh, Cindy Ju Shuan; Atiya, Nadia; Ponnampalavanar, Sasheela; Vadivelu, Jamuna (BMC, 2018)
Background: Burkholderia pseudomallei is the causative agent of melioidosis, which is a potentially life threatening disease endemic in Southeast Asian countries. In Malaysia, cystic fibrosis (CF) is an uncommon condition. The association between CF and B.pseudomallei infections has been reported previously. However, this is the first case report of a pediatric melioidosis relapse and co-infection with other Gram-negative bacteria in Malaysia. Case presentation: A 14-year-old Chinese Malaysian boy presented with a history of recurrent pneumonia, poor growth and steatorrhoea since childhood, and was diagnosed with CF. B. pseudomallei was cultured from his sputum during three different admissions between 2013 and 2016. However, the patient succumbed to end stage of respiratory failure in 2017 despite antibiotics treatment against B.pseudomallei. The isolates were compared using multilocus-sequence typing and repetitive-element polymerase chain reaction (PCR), and confirmed that two of the isolates were of same sequence type, which may indicate relapse. Conclusions: CF patients should be aware of melioidosis in endemic regions, as it is an emerging infectious disease, especially when persistent or recurrent respiratory symptoms and signs of infection occur. The high prevalence rates of melioidosis in Malaysia warrants better management options to improve quality of life, and life expectancy in patients with CF. Travel activities to endemic regions should also be given more consideration, as this would be crucial to identify and initiate appropriate empiric treatment.